2019
DOI: 10.3390/app9132599
|View full text |Cite
|
Sign up to set email alerts
|

HMT-Controlled Synthesis of Mesoporous NiO Hierarchical Nanostructures and Their Catalytic Role towards the Thermal Decomposition of Ammonium Perchlorate

Abstract: In this work, mesoporous nickel oxide (NiO) hierarchical nanostructures were synthesized by a facile approach by hydrothermal reaction and subsequent calcination. The phase structure, microstructure, element composition, surface area, and pore size distribution of the as-prepared products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and the Brunauer-Emmett-Teller (BET) technique. The precursor of Ni 3 (NO 3 ) 2 (OH) 4 nanosheet, Ni 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…8(c), with the FFT pattern revealing the FCC crystalline structure of NiO nanoparticles having a 0.21 nm interplanar distance for the (200) planes in the SWCNT-containing polypyrrole matrix. 71,72 As shown by the selected area electron diffraction (SAED) pattern in Fig. 8(d), the indexed rings corresponding to the (1 1 1), (2 0 0), (2 2 0), and (3 1 1) planes have interplanar spacings of 0.24, 0.21, 0.14, and 0.13 nm, respectively, for the face-centred cubic NiO in the composite, which is consistent with the XRD data.…”
Section: Resultssupporting
confidence: 82%
“…8(c), with the FFT pattern revealing the FCC crystalline structure of NiO nanoparticles having a 0.21 nm interplanar distance for the (200) planes in the SWCNT-containing polypyrrole matrix. 71,72 As shown by the selected area electron diffraction (SAED) pattern in Fig. 8(d), the indexed rings corresponding to the (1 1 1), (2 0 0), (2 2 0), and (3 1 1) planes have interplanar spacings of 0.24, 0.21, 0.14, and 0.13 nm, respectively, for the face-centred cubic NiO in the composite, which is consistent with the XRD data.…”
Section: Resultssupporting
confidence: 82%
“…The synthesis of nickel hydroxide nanostructures was carried out at the n -butanol/water interface, with nickel nitrate in the aqueous phase and urea in the organic phase. Here, urea acts as an alkaline source and undergoes a decomposition reaction at the given temperature to produce ammonia, which then reacts with the precursor to form nickel hydroxide. , The proposed stoichiometric equations for the formation of nickel hydroxide are given below , 6 CO false( NH 2 false) 2 normalC 3 normalH 6 normalN 6 + 6 NH 3 + 3 CO 2 Ni 2 + + 2 NH 3 + 2 normalH 2 normalO Ni false( OH false) 2 + 2 NH 4 + However, it is reported that the concentration of the alkaline source might affect the morphology and physicochemical properties of the final product. , Hence, to study the role of alkaline source in controlling the morphology of the NHs, the concentration of the precursor nickel nitrate was fixed as 1 mmol, and the concentration of urea was altered (6, 12, and 18 mmol) to get the final products NH 1, NH 2, and NH 3, respectively. Both HRSEM analysis (Figure a–c) and HRTEM analysis (Figure d–f) revealed a transformation from a two-dimensional (2D) flake-like morphology to an agglomerated structure with increasing the concentration of urea.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is reported that the concentration of the alkaline source might affect the morphology and physicochemical properties of the final product. 28,29 Hence, to study the role of alkaline source in controlling the morphology of the NHs, the concentration of the precursor nickel nitrate was fixed as 1 mmol, and the concentration of urea was altered (6, 12, It has been reported that increasing the concentration of urea in the reaction mixture causes the release of surplus OH − ions upon hydrolysis, which improves the grain boundaries, increasing the growth of nucleation centers and, thus, the nucleation rate. 30,31 Hence, at a lower urea concentration, as in NH 1, the nucleation process was much slower than the growth rate, resulting in the evolution of relatively larger 2D flakes.…”
Section: Resultsmentioning
confidence: 99%
“…Nickel oxide (NiO) is used as an important semiconductor application material in lithium-ion batteries, electrocatalysis, thermal catalysis, gas sensing, electrochemistry, optical sensing, fuel cell electrodes, and biosensors. 4…”
Section: Introductionmentioning
confidence: 99%
“…Nickel oxide (NiO) is used as an important semiconductor application material in lithium-ion batteries, electrocatalysis, thermal catalysis, gas sensing, electrochemistry, optical sensing, fuel cell electrodes, and biosensors. 4 Nickel oxide (NiO) is a p-type semiconductor with a band gap of 3.6 eV. Nano-scale nickel oxide has attracted a lot of attention due to its excellent physical and chemical properties, and new nanostructures have been made of nickel oxide, e.g., nanoparticles, nanosheets, and nanorods.…”
Section: Introductionmentioning
confidence: 99%